(untitled) (Sains Humanika, 2012)
Practical training is the one of core programme to a higher institution that produces an educational degree. To do so, Faculty of Education, Universiti Teknologi Malaysia (UTM) in collaboration with the Faculty of Islamic Civilisation offer Islamic Studies courses with specialization in Islamic Education. This study examines the students’ perception towards the teaching of Islamic Studies School Training (ISST) undergoing practical training in three different scholls in the district of Batu Pahat, Johore. The study focuses on three aspects that are the attitude and interest of the pupils, perception towards the teaching aids used by ISST and perception towards the techniques of teaching used by ISST. Overall findings show the student’s perception to the teaching of ISST in the above aspects are in positive and high level. A few suggestions to improve the quality of the teaching of the ISST finalise the study.